Congenital heart disease and neuroblastoma: just coincidence?. Issue 1 (1st July 2002) - Holzer, R; Franklin, R C G
Abstract : The clinical history of a neonate with simple transposition of the great arteries in whom a metastatic neuroblastoma was diagnosed incidentally at autopsy is described, and the literature containing all 66 previously reported cases of neuroblastoma associated with congenital cardiac malformations is reviewed. One third of the described cases were classified as in situ neuroblastoma; neural crest derived cardiac lesions were present in 31%. Several possible aetiological mechanisms are discussed, and we conclude that the association of neuroblastoma with congenital cardiac malformations is multifactorial in origin. The described case represents the first reported example in which catecholamine release may have contributed to the fatal outcome of definitive congenital cardiac surgery.